Kebudayaan bagi Pekabaran Injil - Juanda Yulianus (REDOMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2022)
Culture in each region has its own characteristics. But these characteristics do not limit the evangelism is carried out through and within culture. Culture as access in evangelism. The relationship between culture and evangelism is that the evangelist understands the culture and thoughts or beliefs of the local community, then finds the right method to carry out the evangelism. The discussion of this research uses a qualitative method, namely the study of literature. Understanding culture for evangelism is summarized and is a literature study by reading books related to culture for evangelism so that it becomes a new and useful discovery. AbstrakKebudayaan di setiap daerah mempunyai ciri khas tersendiri. Namun ciri khas tersebut tidak membatasi pekabaran Injil dilakukan melalui dan di dalam kebudayaan. Kebudayaan sebagai akses dalam pekabaran Injil. Hubungan antara kebudayaan dengan pekabaran Injil yaitu pemberita Injil memahami kebudayaan dan pemikiran atau kepercayaan masyarakat setempat, kemudian menemukan metode yang tepat untuk melakukan pekabaran Injil. Pembahasan tentang penelitian ini menggunakan metode kualitatif yaitu studi literatur. Memahami kebudayaan bagi pekabaran Injil ini dirangkumkan dan merupakan suatu kajian pustakam dengan cara membaca buku-buku yang berkaitan kebudayaan bagi pekabaran Injil sehingga menjadi suatu penemuan yang baru dan bermanfaat.